Are people in Ifugao Philippines Entrepreneurship? Shedding Light on Entrepreneurial Characteristics, Motivations, Challenges, and Intentions among Ifugao - Client William Malinao (Research Synergy Foundation, 2021)
Entrepreneurship is a means of beginning your own company. A person's target and option depend on those processes of thought. These cycles of thinking and motives either drive or drag the participant to the creative exercises. To fill the gap in the literature, this research explored the entrepreneurial traits, motives, difficulties, and obstacles faced by Ifugao citizens in the Philippines while doing business. The relationship between the above variables and the entrepreneurial aspirations of Ifugao individuals was also calculated. Data were collected from 263 Ifugao persons, both beneficiaries and non-beneficiaries of the programs of various government agencies in the province using the snowball sampling process, through a research questionnaire and semi-structured interview. Using means, the Mann-Whitney U test, and the rank order correlation of Spearman, this paper finds that considering the difficulties and obstacles they face, Ifugao individuals retain the character of becoming an entrepreneur. Overall, five traits that are common to respondents have been identified. Ifugao people stay inspired and it motivates them to persevere constantly in carrying out entrepreneurial practices. Finally, the findings of this study indicate that training, seminars, and workshops, the positive perceived image of entrepreneurs, and motives have a major impact on the entrepreneurial purpose of Ifugao people, which is important for entrepreneurial success.